Interventions For Memory Retention Among Dementia Patients: Systematic Review (Journal of Pharmaceutical Negative Results, 2023)
There is increasing prevalence of dementia patients worldwide. Contemporary cognitive interventions and brain exercises have been adapted to encourage independent cognitive functioning. Novel interventions involving physical and mental faculties are experimented on dementia patients to retain their memory. The primary objective of this review is to identify interventions either cognitive or motor that aimed at improving or maintaining cognitive functioning (especially memory) of dementia patients. Cochrane Library, Medline, CINAHL, PubMed and Google Scholar databases were searched from 2001 to 2023. Two researchers reviewed the potential studies individually for eligibility. Randomized control trials on interventions for dementia patients were included if they clearly described objectives, users and functioning. A systematic review of the studies was carried out. Fifteen studies met the inclusion criteria, and 14 different interventions were identified. With the increasing magnitude of the problem it is necessary to delay the onset and progression of memory decline and promote cognitive functioning. This review is expected to conclude what may work better to preserve the memory of people.